PENGGUNAAN KOMIK DALAM PEMBELAJARAN MATEMATIKA - Karmawati, Karmawati (Hunafa: Jurnal Studia Islamika, 2007)
Mathematics serves as a compulsory subject for elementary pupils. Moreover, it has an excessive frequency of teaching. Therefore, nearly every school hour, pupils learn mathematics. However, most of them always face difficulties in learning it. In fact, some of them hate it. As a result, teachers come to sigh because of their pupils’ difficulties in learning mathematics. The problem is how to solve the problem. This article offers a technique for teaching mathematics through a comic.Kata Kunci: Penggunaan komik, pembelajaran matematika